3(y-1)-(y+2)=7

Simple and best practice solution for 3(y-1)-(y+2)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-1)-(y+2)=7 equation:


Simplifying
3(y + -1) + -1(y + 2) = 7

Reorder the terms:
3(-1 + y) + -1(y + 2) = 7
(-1 * 3 + y * 3) + -1(y + 2) = 7
(-3 + 3y) + -1(y + 2) = 7

Reorder the terms:
-3 + 3y + -1(2 + y) = 7
-3 + 3y + (2 * -1 + y * -1) = 7
-3 + 3y + (-2 + -1y) = 7

Reorder the terms:
-3 + -2 + 3y + -1y = 7

Combine like terms: -3 + -2 = -5
-5 + 3y + -1y = 7

Combine like terms: 3y + -1y = 2y
-5 + 2y = 7

Solving
-5 + 2y = 7

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 2y = 7 + 5

Combine like terms: -5 + 5 = 0
0 + 2y = 7 + 5
2y = 7 + 5

Combine like terms: 7 + 5 = 12
2y = 12

Divide each side by '2'.
y = 6

Simplifying
y = 6

See similar equations:

| x-3+4=-6 | | Y=-5k^2+65k-150 | | 5y^2-1+2(y^2+2)= | | 3x+9=-63-9 | | 3-7(-6p+3)=-p+9 | | -(2y+1)=8(y+2)+2 | | 0.70x+0.30(360-x)=0.60(100) | | 4z+6.1= | | 0.2d-1.2=0.4d+2 | | 5x-2x+9=45-9x | | 4cos^2(x)+8cos(x)-5=0 | | 4+10h=8h+12 | | 18x+-1(8x+-7)=67 | | 188x-(8x-7)=67 | | sin(45-x)=0 | | 2x+X+2x+x=180 | | 2Y+3=6Y-7 | | Y=a^2-8a+15 | | 0.35x+0.40(4)=0.39(x+4) | | 2(x-5)=(5-x) | | 2x^4-x^2-216=0 | | -4(k+3)=6-2k | | 12w=-4 | | 0.2t=0.9t+0.4t | | 11a+18=-2+9a | | 6-(3z-2)=3-4z | | -41+6x=42-x | | 5(x+8)=11 | | -6(5-r)=-60 | | 6y=-5y^3-17y^2 | | 10x-177=95-7x | | 3x-40=2x+10 |

Equations solver categories